Antioxidant Activity and Effect of Sa-khan (Piper, Piperaceae) on the Normal Human Proximal Tubular Epithelial Cell Line - Daorueang, Daoyot (Naresuan University Journal: Science and Technology (NUJST); Vol 28 No 4 (2020): October-December-2020DO - 10.14456/nujst.2020.34, 2020)
The oxidative damage to proximal tubular epithelial cells may lead to renal dysfunction. This research aimed to investigate antioxidant activity of the Sa-khan crude extract (SCE) and evaluated its effect on cell viability of proximal tubular epithelial cells. The total phenolic content of the SCE was determined using Folin-Ciocalteu method. The free radical scavenging activity of the SCE was investigated by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay. The effect of the SCE on HK-2 cells, the human proximal tubular epithelial cell line, was investigated by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The SCE showed the total phenolic content of 17.35 ± 0.40 mg GAE/g extract. In addition, the SCE exhibited scavenging activity on DPPH (IC 50 = 1.15 + 0.071 mg/mL). Moreover, eleven spots of antioxidant compounds were detected when the two-dimensional thin-layer chromatography combined with the DPPH spray technique was performed. Furthermore, the SCE at the concentration of 0.125 mg/mL could promote the proliferation of HK-2 cells over various durations. Together, these results indicate that the SCE may contain compound(s) with potential health benefits. Keywords: Sa-khan, normal human proximal tubular epithelial cell, antioxidant activity